2005
DOI: 10.1242/jeb.01429
|View full text |Cite
|
Sign up to set email alerts
|

Effect of photoperiod on body mass, food intake and body composition in the field vole,Microtus agrestis

Abstract: SUMMARY Many small mammals respond to seasonal changes in photoperiod by altering body mass and adiposity. These animals may provide valuable models for understanding the regulation of energy balance. Here, we present data on the field vole (Microtus agrestis) – a previously uncharacterised example of photoperiod-induced changes in body mass. We examined the effect of increased day length on body mass, food intake, apparent digestive efficiency,body composition, de novo lipogenesis and fatty aci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
52
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(59 citation statements)
references
References 80 publications
(80 reference statements)
6
52
1
Order By: Relevance
“…These data are in line with observations in field voles: switching the day length from 8-to 16-h increased body weight by 24% in 4 wk compared with animals that remained on a day length of 8 h (14). Accordingly, we previously showed that prolonging day length from 12 to 24 h decreases energy expenditure in mice without increasing food intake or locomotor activity (11).…”
Section: Discussionsupporting
confidence: 91%
“…These data are in line with observations in field voles: switching the day length from 8-to 16-h increased body weight by 24% in 4 wk compared with animals that remained on a day length of 8 h (14). Accordingly, we previously showed that prolonging day length from 12 to 24 h decreases energy expenditure in mice without increasing food intake or locomotor activity (11).…”
Section: Discussionsupporting
confidence: 91%
“…This is consistent with our previous results, which indicated that the food intakes of LD and SD voles were not significantly different until day 18 of exposure to LD (above and Król et al 2005). All voles responded to the implantation of mini-osmotic pumps by decreasing their food intake on day 12 compared with day 10.…”
Section: Circulating Leptin Levels and Leptin Resistancesupporting
confidence: 92%
“…, Bartness et al 2002, Morgan et al 2003, Schuhler & Ebling 2006). In the current review, we summarize our work on a novel seasonal model of leptin resistance -the field vole (Microtus agrestis; Król et al 2005Król et al , 2006Król et al , 2007. The review is structured in three parts.…”
Section: Introductionmentioning
confidence: 99%
“…From this the daily N needs for a vole range from 8.7 mg to 19.5 mg N per day. Based on the range of N concentrations in the stomach and a digestibility of the food of 60% the daily food intake that satisfy the N need varies from 3.6 g to 8 g. This is within the range of food intake reported for voles in captivity (Krol et al 2004). The variation in concentrations of N was not reflected in animal performance such as BM or BMI.…”
Section: Discussionmentioning
confidence: 51%